Discrimination and Criticism of Single-Response Models - Henson, Thomas; Box, George; Stewart, Warren (My University, 1996)
Formulas are developed for assessing the probability and adequacy of rival models fitted to a common data set. Cases of full, partial and minimal variance information are treated. The use of the formula is demonstrated with three examples, including a modeling study of a heterogeneous catalytic reaction.